2021
DOI: 10.1002/trc2.12163
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with TNF‐α inhibitors versus methotrexate and the association with dementia and Alzheimer's disease

Abstract: Introduction Peripheral inhibition of tumor necrosis factor (TNF)‐α, outside of the central nervous system, may result in clinical improvement of Alzheimer's disease (AD) outcomes. TNF‐α inhibitors (TNFIs) are effective treatments for various autoimmune conditions and may be effective for preventing and/or treating AD. The objective of this study was to compare the risk of dementia and AD in patients initiating methotrexate versus those initiating TNFIs. Methods Insuran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“… *Kern et al 32 study reported two separate risk estimates based on two different databases and was therefore regarded as two studies in subgroup analyse. bDMARDs, biological disease-modifying anti-rheumatic drugs; ICD, International Classification of Diseases; RA, rheumatoid arthritis; ROBINS-I, Risk of Bias in Nonrandomised Studies of Interventions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… *Kern et al 32 study reported two separate risk estimates based on two different databases and was therefore regarded as two studies in subgroup analyse. bDMARDs, biological disease-modifying anti-rheumatic drugs; ICD, International Classification of Diseases; RA, rheumatoid arthritis; ROBINS-I, Risk of Bias in Nonrandomised Studies of Interventions.…”
Section: Resultsmentioning
confidence: 99%
“… *Kern et al 32 study reported two separate risk estimates based on two different databases and was therefore regarded as two studies in subgroup analyse. …”
Section: Resultsmentioning
confidence: 99%
“…Relatively few epidemiological studies have so far investigated treatment with TNFi and incident dementia [ 10 16 ]. The available data suggest that TNFi may be promising candidates for the treatment of dementia, but there are methodological limitations to the prior studies in terms of the observation period and study design [ 11 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Comparing TDMARDs with nonuse or even with nonbiologic DMARDs is subject to severe bias due to confounding, as the decision to initiate treatment with TDMARDs in old age is likely influenced by RA activity and frailty, which cannot be fully measured with claims data. 44 Some active comparators, for instance methotrexate, which was used in another recent study as a comparator to TNF inhibitors, 45 are likely more appropriate than nonuser comparisons owing to improved confounding adjustment. Indeed, the study comparing TNF inhibitors to methotrexate found no differences in the risk of dementia, unlike previous studies comparing TNF inhibitors with nonuse.…”
Section: Discussionmentioning
confidence: 99%